LAND CONVERSION AND THE LEVEL COMMUNITY SOCIAL COHESION IN SUB-DISTRICT EMPOANG JENEPONTO REGENCY - Faisal, Muhammad (Sosiohumaniora, 2020)
This research aims to find out land conversion that occurs and analyze relationship between the level social cohesion and collective action community after function of the land. The type research used is quantitative research, because takes samples from one population and uses questionnaire basic data collection tool. The number respondents ware 74 people consisting 68 men and 6 women who were captured by convenience, incidental, and purposively sampling techniques taken from those who had sold land and came from various RWs in Empoang subdisrict. Data analysis using SPSS for Windows 20 application. Test hypothesis using Rank Spearman statistical test. The results study found land conversion occurs because land is less productive and also form demographic adaptation and multi-form conversion. Spearman rank test resultsare obtained sig (2-tailed) value 0.013 which is smaller than alpha 0.05. This explains there is positive relationship between the levelof social cohesion and level community involvement collective action, although the correlation coefficient is only 0.286 which explains the relationship between variables is weak. If the level of variable social cohesion increases, level of community involvement in collective action also increases even though the level increase is low due to the typerelationship between the weak variables.